Perancangan Dan Implementasi Website Informasi Nagari Koto Tangah - Irman Efendi; Shintia Khairunnisa (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to design and develop a web-based information system for Nagari Koto Tangah in order to enhance the speed and ease of information dissemination to the public in an effective and efficient manner. A descriptive research method was employed, with data collection techniques including surveys using questionnaires that emphasize internal control systems. In addition, supporting data were gathered through field observations, literature reviews, and analysis of current conditions in the field. This research not only focuses on the system development process, but also seeks to compare theoretical frameworks with real-world practices implemented at the Nagari Koto Tangah Office. Moreover, it aims to provide recommendations for improving the quality of public information services in the future.